PEGARUH ATRIBUT PRODUK DAN BAURAN PROMOSI TERHADAP MINAT BELIâ€. (STUDI KASUS PEMBALUT WANITA SOFTEX PADA MALL BLOK M SQUARE KEBAYORAN BARU. JAKARTA SELATAN)â€ - Hendarsih, Ida; Harjunawati, Sri (Yayasan Akrab Pekanbaru, 2019)
This study discusses the effect of product attributes and promotion mix on softex sanitary buying interest in Blok M Mall, South Jakarta. The aim is to find out the factors that influence consumer buying interest. Because at this time the increasingly fierce product competition in the sanitary napkin business, with the emergence of new brands. The analytical method used is research The method used is a quantitative method. The sampling technique used was the simple random sampling method, which is a sampling technique that was randomly random sampling, the number of respondents was 150 people. Data collection by observation, documentation and questionnaire. Testing indicators or questionnaires from calculations using SPSS 20. From the results of the analysis there is a significant effect between product attributes and promotion mix on buying interest. The results of this study indicate that product attributes and promotion mix of positive relations to buying interest with multiple correlation analysis coefficients indicate the Adjusted R Square number of 0.851 this means 85.1% from consumer buying interest can be explained by the variation of the two independent variables namely product attributes and promotion mix, while the remaining 14.9% consumer buying interest is influenced by other variables.